2017
DOI: 10.1038/srep40058
|View full text |Cite
|
Sign up to set email alerts
|

Aligned copper nanorod arrays for highly efficient generation of intense ultra-broadband THz pulses

Abstract: We demonstrate an intense broadband terahertz (THz) source based on the interaction of relativistic-intensity femtosecond lasers with aligned copper nanorod array targets. For copper nanorod targets with a length of 5 μm, a maximum 13.8 times enhancement in the THz pulse energy (in ≤20 THz spectral range) is measured as compared to that with a thick plane copper target under the same laser conditions. A further increase in the nanorod length leads to a decrease in the THz pulse energy at medium frequencies (≤2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 47 publications
(74 reference statements)
1
21
0
Order By: Relevance
“…Laser interaction with NCPs in such intensity regime could be appealing due to the increased absorption efficiency provided by the NCP, which could allow to observe or to enhance physical phenomena that would otherwise require higher laser intensities and, thus, larger and more expensive facilities. For this reason, for the lowest laser intensity case, we also investigate the effect of different nanostructure morphologies, considering two structures of wide experimental interest in the laser-plasma community and in materials science: foams 5 , 10 , 12 , 13 and nanowires 46 – 48 , 52 , 53 , 55 , 56 . The relevance of the investigation of how these kinds of nanostructured materials behave in extreme electromagnetic fields goes beyond the generation of NCPs, being of interest for both fundamental science 57 and specific applications 47 , 48 .…”
Section: Introductionmentioning
confidence: 99%
“…Laser interaction with NCPs in such intensity regime could be appealing due to the increased absorption efficiency provided by the NCP, which could allow to observe or to enhance physical phenomena that would otherwise require higher laser intensities and, thus, larger and more expensive facilities. For this reason, for the lowest laser intensity case, we also investigate the effect of different nanostructure morphologies, considering two structures of wide experimental interest in the laser-plasma community and in materials science: foams 5 , 10 , 12 , 13 and nanowires 46 – 48 , 52 , 53 , 55 , 56 . The relevance of the investigation of how these kinds of nanostructured materials behave in extreme electromagnetic fields goes beyond the generation of NCPs, being of interest for both fundamental science 57 and specific applications 47 , 48 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, arrays of Si micro-wires irradiated by ultra-short joule-class laser pulses ( I ~ 1 × 10 21 W/cm 2 ) have generated electron beams with increased total and cut-off energies, from 30 to 70 MeV 23 . Furthermore, it has also been demonstrated that aligned Cu-nanorod arrays irradiated by sub-joule ultra-short laser pulses ( I ~ 3.5 × 10 18 W/cm 2 ) can generate intense broadband terahertz sources 24 .…”
Section: Introductionmentioning
confidence: 99%
“…First theoretical and numerical estimations made by Wang et al 43 have shown that this target type allows for an enhanced laser energy absorption. The same nanowire geometry has been demonstrated experimentally to be very effective for enhanced THz pulse generation 44 , and several other works have demonstrated enhanced X-ray emission though greater electron heating with nano-velvets 45 and nanowires 46 48 . The high aspect ratio between length and diameter of NWs favors an increased laser absorption due to a greater effective interaction surface area with the incoming electromagnetic (EM) wave, occurring within a few laser cycles such as to maximize the interaction with the intact NW forest.…”
Section: Introductionmentioning
confidence: 86%